Ali & Ava [videorecording (DVD)] - Barnard, Clio; Akhtar, Adeel; Rushbrook, Claire; Torchia, Ellora, 1992-; Thomas, Shaun, 1997-; Gavin, Natalie (Actress); Goodwin, Mona; Pattani, Krupa; Dhillon, Vinny; Connor, Tasha; Shackleton, Macy; Bodorová, Ariana (Greenwich Entertainment, 2022)
Sparks fly as two people develop a deep connection despite the lingering legacy of past relationships. A compelling love story enveloped in music and imbued with humor. BAFTA nominee for Best British Film.